Pengaruh Penggunaan Metode Scramble Terhadap Keterampilan Membaca Permulaan Pada Anak TK Kelompok B - Farlina Hardianti; Rokyal Harjanty (Peneliti.net, 2020)
This study were aimed: (1) to know the effect of using scramble method in basic reading skill of the kindergarden students group B. (2) to know the effectiveness of the scramble method in basic reading skill of the kindergarden students group B. The type of research that used was quasi experimental study, with Pre-Test Post-Test Control Group Design. The population of this study were all students of group B TK Pertiwi Selong and the sample were student of groups B1 and B2. The technique of data collection were using interview, validation of research instrument and observation. The data analysis in this study was used an independent sample t test with a significance level of 0.05. The results showed that there were the differences in the final results after being given treatment between the results of the control class and the experimental class with a percentage of 70.83% in the experimental class and 56.49% in the control class. The t-test results showed p <0.05, namely p = 0.024, so it can be concluded that the scramble method is effective to use in the beginning of reading skills of group B children.